Land flatworms (Platyhelminthes, Geoplanidae) of São Tomé: a first account on their diversity, with the description of five new species - Sluys, Ronald; Neumann, Matthias; Lima, Ricardo F. De; Drewes, Robert C. (Zootaxa, 2017)
The present contribution provides the first faunistic and taxonomic account of six species of land flatworm from the island of São Tomé, including five new species of the genus Othelosoma Gray, 1869 and the introduced Bipalium kewense Moseley, 1878. One of the new species represents the first African land flatworm that has specks on its dorsal body surface, instead of stripes or a more or less uniform colouration. At least two of the new species were observed to prey on snails. The study details the fourth record of a sclerotic spermatophore in a species of land flatworm, and discusses the definition and homology of double female genital canals in African and Indian species of the genus Othelosoma.